Criminal minds. The sixth season [videorecording (DVD)] - Davis, Jeff, 1975- (CBS Paramount Network Television, 2011)
The members of the Behavioral Analysis Unit (BAU) profile uncatchable crooks responsible for unthinkable crimes. Team leader Aaron Hotchner and profiling expert David Rossi face a deadly challenge when a new case threatens one of their own. Special Agent Emily Prentiss takes on an enemy from her past in a game of cat-and-mouse, and nothing will ever be the same. Features 24 thrillingly suspenseful episodes, plus deleted scenes, featurettes, a gag reel, and more.